Celowość i efektywność koncepcji zarządzania wartością przedsiębiorstwa (VBM) - Dudycz, Tadeusz; Szymański, Piotr (Value-Based Management - Appropriateness and Effectiveness, 2006)
Value-based management programs in practice focus too much on measurement and too little on management activities that create shareholder value. It makes these programs seem to be simple, Results from research reveal that putting VBM to practice is far more complicated than many of its proponents make it out to be. Therefore the authors show real effects of VBM for enterprises, point at main activities which are necessary to get results and also indicate typical problems with implementation of this conception.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 271-280